INTEGRASI HUKUM ISLAM DAN HUKUM POSITIF DALAM PENANGANAN BULYYING DI PONDOK PESANTREN AL-HIDAYAH CIOMAS - Asy-Syifa Sudjiman; Ana Rodiana; Rosipah; Farhan Fadilah; Rafli Ramadhani; Rifky Nurwahyu Budi Utomo (Universitas Negeri Malang, 2025)
This study aims to analyze the integration of Islamic law and positive (national) law in addressing bullying cases at Al-Hidayah Islamic Boarding School in Ciomas by employing a qualitative approach, with data obtained through in-depth interviews, observation, and documentation; the findings reveal that while Islamic legal principles—such as the prohibition of injustice and the obligation to uphold others’ rights—are normatively applied, their practical implementation lacks structured mechanisms as prescribed in positive law, particularly the Child Protection Act and Ministry of Education Regulation No. 82 of 2015, thereby necessitating a more systematic integration between both legal frameworks to establish internal pesantren regulations that can prevent and handle bullying effectively, fairly, and in accordance with Islamic values as well as national legal standards.